Recovery of Recombinant Avian Paramyxovirus Type-3 Strain Wisconsin by Reverse Genetics and Its Evaluation as a Vaccine Vector for Chickens - Mohamed A. Elbehairy; Sunil K. Khattar; Siba K. Samal (Viruses, 2021)
A reverse genetic system for avian paramyxovirus type-3 (APMV-3) strain Wisconsin was created and the infectious virus was recovered from a plasmid-based viral antigenomic cDNA. Green fluorescent protein (GFP) gene was cloned into the recombinant APMV-3 genome as a foreign gene. Stable expression of GFP by the recovered virus was confirmed for at least 10 consecutive passages. APMV-3 strain Wisconsin was evaluated against APMV-3 strain Netherlands and APMV-1 strain LaSota as a vaccine vector. The three viral vectors expressing GFP as a foreign protein were compared for level of GFP expression level, growth rate in chicken embryo fibroblast (DF-1) cells, and tissue distribution and immunogenicity in specific pathogen-free (SPF) day-old chickens. APMV-3 strain Netherlands showed highest growth rate and GFP expression level among the three APMV vectors in vitro. APMV-3 strain Wisconsin and APMV-1 strain LaSota vectors were mainly confined to the trachea after vaccination of day-old SPF chickens without any observable pathogenicity, whereas APMV-3 strain Netherlands showed wide tissue distribution in different body organs (brain, lungs, trachea, and spleen) with mild observable pathogenicity. In terms of immunogenicity, both APMV-3 strain-vaccinated groups showed HI titers two to three fold higher than that induced by APMV-1 strain LaSota vaccinated group. This study offers a novel paramyxovirus vector (APMV-3 strain Wisconsin) which can be used safely for vaccination of young chickens as an alternative for APMV-1 strain LaSota vector.